KITÂBATU HURÛFIL HAMZATI FIL QUR’ÂNIL KARÎM - Muhammad Syarifuddin; Moh. Nasikin; Andri Warseto (Universitas Islam Negeri Mataram, 2021)
This scientific journal or newspaper aims to answer the following questions (1) Howto write the letters of the hamza at the beginning of the word, (2) How to write theletters of the hamza in the middle of the word, (3) How to write the letters of thehamza at the end of the word. As for the method that the researcher uses, it is thelibrary studies method, which started from collecting information and data about thehamza letters, dividing them and writing them, then analyzing and arranging themaccording to the research requirements and hypothesis. The results of the researchare as follows: (1) The hamza in the beginning of the word is written in the form ofAlif . (2) The hamza in the middle of the word is written on the waw andon the accent <e> and on its own <e>. (3) The hamza at the end of the word iswritten on the alif , the accent <e> and on its own <e>.